2010
DOI: 10.1149/1.3446852
|View full text |Cite
|
Sign up to set email alerts
|

Lithium–Air Batteries Using SWNT/CNF Buckypapers as Air Electrodes

Abstract: Li-air cells based on Li foil as an anode electrode, freestanding carbon nanotube/nanofiber mixed buckypaper as an air ͑cathode͒ electrode, and organic electrolyte were assembled. The air electrode was made with single-wall carbon nanotube ͑SWNT͒ and carbon nanofiber ͑CNF͒ without any binder. The discharge capacity was strongly dependent on both the discharge current density and the thickness of the air electrode. A discharge capacity as high as 2500 mAh/g was obtained for an air electrode at a thickness of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
158
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(169 citation statements)
references
References 13 publications
11
158
0
Order By: Relevance
“…Zhang et al reported that thicker electrodes delivered lower specifi c capacity. [ 34 ] This performance is attributed to slow oxygen diffusion through electrodes immersed in electrolytes. Scanning electron microscopy (SEM) images of the surfaces of the air electrode of a fully discharged cell showed that the voids on the air side were almost fully fi lled by solid deposition; however, the voids on the separator side were still wide open.…”
Section: Electrode Architecturementioning
confidence: 99%
“…Zhang et al reported that thicker electrodes delivered lower specifi c capacity. [ 34 ] This performance is attributed to slow oxygen diffusion through electrodes immersed in electrolytes. Scanning electron microscopy (SEM) images of the surfaces of the air electrode of a fully discharged cell showed that the voids on the air side were almost fully fi lled by solid deposition; however, the voids on the separator side were still wide open.…”
Section: Electrode Architecturementioning
confidence: 99%
“…[ 14,15 ] Many researchers are now focusing on the development of advanced catalysts and cathode substrates to improve effi ciency and cycle life using mostly organic electrolytes. Materials used as cathode supports comprise porous carbon, [16][17][18][19] graphene, [ 20 ] carbon nanotubes (CNT) or carbon nanofi bers (CNF) [ 21,22 ] with catalysts such as metal oxides (MnO 2 , [23][24][25][26] Co 3 O 4 , [ 27,28 ] noble metals, [ 7,[29][30][31] and others. [ 32,33 ] At an industrial level, in 2009 IBM launched the "Battery 500" project, which had the ambitious aim of developing a Li/air battery that could ensure a 500 mile driving range, [ 34 ] and it was thought that soon enough this technology would make it to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded from the gure with EIS spectra, that the diameter of semi-circles, is increasing due to pulverization of electrodes after each cycle, and this leads to loss of electronic contact between electrolyte and electrodes. In spite of fact that EC/DEC/LiPF 6 electrolyte leads to production of higher electronic contact resistance, analysis after the discharge process has revealed, that the higher resistance is caused by the blocking of the air cathode by Li 2 O 2 , Li 2 CO 3 and nano Al 2 O 3 particles on the air side, after the electrochemical cycling test [6]. The discharge capacity of the nanocomposite EC/DEC/LiPF 6 /5 wt.% Al 2 O 3 yielded lower values, since the nano particles decreased the reaction and led to blocking of GDL cathode air breathing pores and also resulted in increasing contact resistance of the electrodes, because of insulating nature of the nano ceramic powders.…”
Section: Resultsmentioning
confidence: 99%